Carbohydrate Kinase (RhaK)-Dependent ABC Transport of Rhamnose in Rhizobium leguminosarum Demonstrates Genetic Separation of Kinase and Transport Activities - Rivers, Damien (American Society for Microbiology, 2013)
In Rhizobium leguminosarum the ABC transporter responsible for rhamnose transport is dependent on RhaK, a sugar kinase that is necessary for the catabolism of rhamnose. This has led to a working hypothesis that RhaK has two biochemical functions: phosphorylation of its substrate and affecting the activity of the rhamnose ABC transporter. To address this hypothesis, a linker-scanning random mutagenesis of rhaK was carried out. Thirty-nine linker-scanning mutations were generated and mapped. Alleles were then systematically tested for their ability to physiologically complement kinase and transport activity in a strain carrying an rhaK mutation. The rhaK alleles generated could be divided into three classes: mutations that did not affect either kinase or transport activity, mutations that eliminated both transport and kinase activity, and mutations that affected transport activity but not kinase activity. Two genes of the last class (rhaK72 and rhaK73) were found to have similar biochemical phenotypes but manifested different physiological phenotypes. Whereas rhaK72 conferred a slow-growth phenotype when used to complement rhaK mutants, the rhaK73 allele did not complement the inability to use rhamnose as a sole carbon source. To provide insight to how these insertional variants might be affecting rhamnose transport and catabolism, structural models of RhaK were generated based on the crystal structure of related sugar kinases. Structural modeling suggests that both rhaK72 and rhaK73 affect surface-exposed residues in two distinct regions that are found on one face of the protein, suggesting that this protein's face may play a role in protein-protein interaction that affects rhamnose transport.